Diagnostic potential of miRNA-135A1 in human papillomavirus associated cervical lesions - D. S. Elkin; M. I. Taubinskaya; N. V. Elkina; R. S. Faskhutdinov; M. D. Fedorova; A. N. Katargin; K. I. Zhordania; E. A. Mustafina; E. A. Grivachev; L. S. Pavlova; S. V. Vinokurova (Успехи молекулярной онкологии)
Introduction. Human papillomavirus (HPV) infection with high-risk HPVs is an etiological factor in the development of cervical cancer, with HPV type 16 (HPV16) being the most common. The mechanisms leading to disruption of viral oncogene expression and initiation of epithelial cell transformation are poorly understood. Epigenetic regulatory factors, including cellular miRNAs, may play an important role in HPV-induced carcinogenesis, and aberrantly expressed miRNAs may be promising markers for the diagnosis of HPV-associated lesions.Aim. To search for miRNAs involved in the pathogenesis of HPV16-associated cervical cancer and to evaluate their diagnostic potential for the detection of cervical cancer and precancerous lesions.Materials and methods. MiRNA expression in clinical samples was assessed by both next generation sequencing and quantitative stem-loop polymerase chain reaction (sl-qPCR). Plasma miRNAs from patients with precancerous and cancerous lesions and healthy donors were analyzed using sl-qPCR. Loss of heterozygosity in cervical cancer samples was assessed by copy number ratio of MIR135A1 and ACTB genes. A total of 67 patients with cervical cancer, 21 with precancerous cervical lesions and 24 healthy donors were included in the study. The effect of DNA methylation on miRNA-135A1 expression was evaluated after treatment with a demethylating agent of the cervical HPV16-positive SiHa cell line. Changes in the expression of the HPV16 E6 oncogene were analyzed after transfection with synthetic analogues of the mature forms of miRNA-135А1 (miRNA-135a-3p and miRNA-135a-5p).Results. A significant decrease in the expression of miRNA-135A1 and miRNA-135A2 was detected in tumor tissue samples from HPV16-positive cervical cancer, which was confirmed by sl-qPCR in an independent panel of tumor samples. A decrease in miRNA-135A1 expression was shown to result from both loss of heterozygosity of the gene and aberrant DNA methylation. Transfection of mature forms of miRNA-135A1 into SiHa cells resulted in decreased expression of the E6 oncogene of HPV16. Blood plasma samples from patients with cervical cancer and precancerous lesions showed lower levels of miRNA-135a-3p than healthy donors, and ROC analysis indicated its high diagnostic potential.Conclusion. Levels of miRNA-135A1 are significantly reduced in cervical lesions, both in tumor tissue and plasma, and the ability of this miRNA to suppress the expression of the HPV16 E6 oncogene suggests its oncosuppressive properties. Thus, miRNA-135A1 can be used as a promising new marker for the diagnosis of HPV-associated lesions.